Implementasi Praktikum Berbasis Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Dan Sikap Ilmiah Siswa - Erni Johar; Sulistyono Sulistyono; Anna Fitri Hindriana (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
The focus of the problem in this study is student's low learning achievement and scientific attitude on the subject of Respiratory System. To anticipate these problems, it is necessary some effort to improve the student's learning achievement and scientific attitudes, by implementing the Guided Inquiry-Based Practicum. The research method used a combination methods of research (mixed methods), which uses the design of Exploratory Design. This study used two treatment groups, experimental class (class VIII-E, 34 students) implementing guided inquiry-based practicum, and control class (class VIII-A, 34 students) using ordinary practicum. Instrument used in this research are observation sheet of learning implementation, learning result test, student performance test, and student response questionnaire to implementation of guided inquiry based practicum. The result of descriptive analysis shows that the mean score of the student's learning achievement of experimental class is 75,59 and the control class is 61,18. The result of research data used t-test Paired Sample. Based on hypothesis test results obtained sig.0.000 <α (0,05) then H0 rejected and H1 accepted. Thus it can be concluded that the implementation of guided inquiry-based practicum can improve learning achievement and scientific attitudes of students of SMPN 2 Plered on the subject of human respiratory systemKeywords: Guided Inquiry; Based Practicum; Learning Achievements; Scientific Attitudes